Amplified Spontaneous Emission and Random Lasing in MAPbBr3 Halide Perovskite Single Crystals. Issue 17 (8th June 2020) - Murzin, Aleksei O.; Stroganov, Boris V.; Günnemann, Carsten; Hammouda, Samia Ben; Shurukhina, Anna V.; Lozhkin, Maxim S.; Emeline, Alexei V.; Kapitonov, Yury V.
Abstract: Halide perovskites are a promising optical gain medium with high tunability and simple solution synthesis. In this study, two gain regimes, namely, amplified spontaneous emission and random lasing, are demonstrated in the same MAPbBr3 halide perovskite single crystal. For this, photoluminescence is measured at a temperature of 4 K with pulsed femtosecond pumping by UV light with an 80 MHz repetition rate. Random lasing is observed in areas of the sample where a random resonator is formed due to cracks and crystal imperfections. In more homogeneous regions of the sample, the dominant regime is amplified spontaneous emission. These two regimes are reliably distinguished by the line width, the mode structure, the growth of the intensity after the threshold, and the degree of polarization of the radiation. The spectral localization of the stimulated emission well below the bound exciton resonance raises a question concerning the origin of the emission in halide perovskite lasers. Abstract : Amplified spontaneous emission and random lasing regimes are differentiated in the photoluminescence from MAPbBr3 single crystals at 4 K and pulsed UV pumping. These two regimes are differentiated by the line width, mode structure, and polarization of the emission, and its growth after the threshold.